Kesadaran merek, citra merek, persepsi terhadap kualitas dan pengaruhnya terhadap niat beli sepeda motor Honda Vario di Surabaya - Geby Laylany Widjanarko; Soni Harsono (STIE Perbanas Surabaya, 2019)
Brand awareness, brand image, and highquality perception can lead the company to have a competitive advantage over a product in creating a relationship between consumers and producers. This study aims to examine and analyze the influence of brand awareness, brand image, and felt- quality towards the purchase intention Honda Vario motorcycle in Surabaya. By using purposive sampling obtained 130 respondents, using multiple linear regression for data analysis and validity, reliability and classical assumption tests have been carried out, this study proves that brand awareness, brand image, perceived quality affect purchase intentions both partially and simultaneously. Because this study has direct implications for purchase intentions, there are several indicators of brand awareness, brand image and quality that are felt to be lacking, should get attention from manufacturers, distributors and dealers.